Listening Strategies Used by English Language Education Program Students in an Online Academic Listening Course - Elmi Erinta; Listyani Listyani (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. There has been extensive research done on learning strategies nowadays. A lot of researchers are interested to know which strategies are commonly used by EFL learners. They perceive the importance of this study. This research was therefore done to investigate the strategies used by English Language Education Program students in an online Academic Listening course. This study employed a qualitative method. To find out the answer, questionnaires that consisted of some close-ended and open-ended questions were used. The questionnaire was distributed to 34 students of the 2020 batch, who were taking an online Academic Listening class. Interviews with some students to gain further information and who had unique answers were also conducted. The results showed that in the online listening class, the students used six strategies, those were metacognitive, cognitive, memory, compensatory, social, and affective strategies. The findings also showed that metacognitive and cognitive strategies were mostly used strategies by students. Keywords: academic listening, listening strategies, online learningAbstrak. Telah banyak penelitian dilakukan terkait dengan strategi pembelajaran. Banyak peneliti tertarik untuk mengetahui strategi belajar apakah yang umum digunakan oleh para siswa yang belajar Bahasa Inggris sebagai bahasa asing. Para peneliti memandang pentingnya hal ini. Oleh karena itu, penelitian ini dilakukan untuk mengetahui strategi yang digunakan oleh mahasiswa program Pendidikan Bahasa Inggris pada mata kuliah online Academic Listening. Data yang diambil dengan menggunakan metode kualitatif. Untuk mendapatkan jawaban, kuesioner yang berisi beberapa pertanyaan terbuka dan tertutup. Kuesioner dibagikan kepada 34 mahasiswa angkatan 2020, dimana mereka sedang mengambil mata kuliah tersebut. Dilakukan interview pada beberapa siswa untuk mendapat informasi mendalam dan mahasiwa dengan jawaban yang menarik atau kurang jelas. Hasil jawaban menunjukkan bahwa di kelas online Academic Listening, mahasiswa menggunakan 6 strategi yaitu metakognitif, kognitif, memori, kompensatori,sosial, dan afektif. Temuan ini menunjukkan bahwa metakognitif dan cognitif strategi adalah strategi yang sering digunakan mahasiswa. Kata kunci: akademik listening, strategi mendengarkan, pembelajaran online